When inefficiency begets efficiency - Gersbach, Hans; Haller, Hans (IHS economics series, 2003)
Collective consumption decisions taken by the members of a household may prove inefficient. The impact of such inefficient household decisions on market performance is investigated. At one extreme, market efficiency can occur even when household decisions are inefficient, namely when household inefficiencies are merely due to inefficient net trades with the market. At the other extreme, market efficiency is bound to fail, if household inefficiencies are solely caused by an inefficient distribution of a household's aggregate consumption to its individual members. This leads us to consider competitive forces as a disciplinary device for households. When households compete for both resources and members then household stability requires efficient or not too inefficient internal distribution. -- allocative efficiency ; general equilibrium ; household behavior
Keywords: Arbeitspapier; Graue Literatur; Gleichgewichtsmodell; Markteffizienz; Effizienz; Verbraucherverhalten; Haushalt